Reduced β-cell function in early preclinical type 1 diabetes. Issue 3 (March 2016) - Koskinen, Maarit K; Helminen, Olli; Matomäki, Jaakko; Aspholm, Susanna; Mykkänen, Juha; Mäkinen, Marjaana; Simell, Ville; Vähä-Mäkilä, Mari; Simell, Tuula; Ilonen, Jorma; Knip, Mikael; Veijola, Riitta; et al.
Abstract : Objective: We aimed to characterize insulin responses to i.v. glucose during the preclinical period of type 1 diabetes starting from the emergence of islet autoimmunity. Design and methods: A large population-based cohort of children with HLA-conferred susceptibility to type 1 diabetes was observed from birth. During regular follow-up visits islet autoantibodies were analysed. We compared markers of glucose metabolism in sequential intravenous glucose tolerance tests between 210 children who were positive for multiple (≥2) islet autoantibodies and progressed to type 1 diabetes (progressors) and 192 children testing positive for classical islet-cell antibodies only and remained healthy (non-progressors). Results: In the progressors, the first phase insulin response (FPIR) was decreased as early as 4–6 years before the diagnosis when compared to the non-progressors ( P =0.001). The difference in FPIR between the progressors and non-progressors was significant ( P <0.001) in all age groups, increasing with age (at 2 years: difference 50% (95% CI 28–75%) and at 10 years: difference 172% (95% CI 128–224%)). The area under the 10-min insulin curve showed a similar difference between the groups ( P <0.001; at 2 years: difference 36% (95% CI 17–58%) and at 10 years: difference 186% (95% CI 143–237%)). Insulin sensitivity did not differ between the groups. Conclusions: FPIR is decreased several years before the diagnosis of type 1 diabetes, implying an intrinsic defect in β-cell mass and/or function.